Nilai Tukar Petani Padi di Beberapa Sentra Produksi Padi di Indonesia - Tjetjep Nurasa; Muchjidin Rachmat (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2013)
EnglishContinuity of farming and rice production is determined by rice farmers’ interest and welfare. One of the measurement instruments used are Rice Farmers Terms of Trade (FTT-Rice). Rice Farmers Terms of Trade will encourage farmers to produce rice. In the period of 2006-2008 FTT-Rice in West Java and North Sumatra decreased while that in South Sulawesi increased. Further investigation showed a decrease in FTT - Rice in West Java was caused by a decrease in the FTT-Consumption. On the other hand, rice production cost increased. In North Sumatra, the FTT-Rice decline occurred not only on consumer goods but also on production cost. While in Sulawesi an increase in FTT-Rice was due to the increase in FTT-Rice to all components in the group either consumption or production cost. From the analysis of Subsistence Rice Terms of Trade (FTTS-Rice) showed that the average rice production accounted for 56.42 percent of the farm household expenditures. Food expense was the households’ largest expenditure, while the lowest spending is that for communication. Labor cost was the largest proportion of the production cost, while the cost of other production inputs was relatively small. The FTT-Rice fluctuates monthly, i.e., the lowest was found on April and May along with the period of paddy harvest and lowest price of rice. The highest FTT-Rice took place from December to January during off season. This study implies :(a) increased production of rice was not always followed by an increase in FTT-Rice and it even resulted in a decreased FTT because the measurement was only based on FTT-Rice to price ratio; (b) it is important to maintain effectiveness of the floor price policy for price in order to stabilize the selling price of rice at farm level; and (c) it is necessary to offer credit to farmers, such as warehouse receipt, to encourage farmers to delay rice selling after harvest. Improving the FTT does not depend on the agricultural policy only, but also related with policies of non-agricultural sectors. Floor price policy for rice should be adjusted in accordance with dynamics of consumer product prices.IndonesianKelangsungan usatahani dan produksi padi sangat ditentukan oleh kegairahan dan kesejahteraan petani padi dalam berusahatani padi. Salah satu alat ukur yang dapat dipakai adalah Nilai Tukar Petani Padi (NTP-Padi). Nilai tukar petani padi yang meningkat akan mendorong kegairahan petani dalam berusahatani memproduksi padi. Dalam tahun 2006-2008, NTP-Padi di Jawa Barat dan di Sumatera Utara menurun sedangkan di Sulawesi Selatan menunjukkan peningkatan. Penelusuran lebih lanjut menunjukkan penurunan NTP-Padi di Jawa Barat terutama disebabkan oleh penurunan NTP-Padi terhadap konsumsi sementara NTPpadi terhadap biaya produksi dan modal cenderung meningkat. Di Sumatera Utara, penurunan NTP-Padi terjadi tidak hanya terhadap barang konsumsi tetapi juga terhadap komponen biaya produksi. Sementara di Sulawesi peningkatan NTP-Padi terjadi karena adanya peningkatan NTP-Padi terhadap semua komponennya baik pada kelompok konsumsi maupun kelompok biaya produksi. Dari analisis Nilai Tukar Subsisten Padi (NTS-Padi) menunjukkan bahwa secara rata-rata usahatani padi memberikan kontribusi sebesar 56,42 persen dalam pemenuhan pengeluaran rumah tangga petani. Pengeluaran untuk makanan merupakan pengeluaran terbesar rumah tangga sedangkan komunikasi merupakan pengeluaran yang terendah. Sementara itu dalam biaya produksi, biaya tenaga kerja merupakan komponen terbesar dalam biaya produksi usahatani padi, sementara biaya input produksi lainnya (pajak) relatif kecil. Nilai tukar petani padi cenderung fluktuatif antar bulan berada paling rendah pada bulan April–Mei sejalan dengan masa panen padi dan harga padi pada nilai yang rendah, sedangkan NTP-Padi tertinggi terjadi pada masa maceklik yaitu bulan Desember-Januari. Kondisi ini memberikan implikasi bahwa: (a) peningkatan produksi petani tidak selalu diikuti oleh peningkatan NTP dan bahkan cenderung berakibat penurunan NTP karena pengukuran NTP hanya didasarkan kepada rasio harga harga, (b) pentingnya menjaga efektivitas kebijakan harga dasar gabah dalam rangka menjaga stabilitas harga jual padi petani, dan (c) perlunya pengembangan sistem pendanaan untuk penundaan masa penjualan gabah petani. Peningkatan kesejahteraan petani padi tidak hanya ditentukan oleh kebijakan dibidang pertanian juga nonpertanian. Untuk itu kebijakan penetapan harga dasar gabah harus selalu disesuaikan sejalan dengan pergerakan harga produk konsumsi.